(untitled) (Eurasian Journal of Physics,Chemistry and Mathematics, 2024)
Article on the history of development of nanotechnologies, author Uktam Dekhkonovich Sherkulov, Republic of Uzbekistan, Navoi State Pedagogical Institute. The article describes what nanotechnology is, the emergence of nanotube research, the creation of electron microscopes, Feynman’s lecture, the results of research by world scientists, and a lot of historical information. The article is intended for scientific researchers and graduate students.